Brain abscess caused by Streptococcus pyogenes with atypical symptoms: a case report and literature review - Chun-Zhen Hua; Zhi-Peng Shen; Ming-Ming Zhou; Can Lai; Guan-Nan Bai; Wei-Zhong Gu; Yong-Ping Xie; Jin-Si Zhou; Wei-Lin Hu; Qiang Shu (BMC, 2024)
Abstract Background Streptococcus pyogenes is a common gram-positive bacterium, belonging to group A Streptococcus (GAS), and is responsible for causing a range of clinical conditions. Brain abscess caused by GAS is uncommon in pediatric infectious diseases, and GAS brain abscess without acute infectious symptoms has been rarely reported. Case presentation We present a case of one GAS brain abscess in a previously healthy child with unusual clinical manifestations of decreased muscle strength in the left limbs. The right frontal lobe mass lesion was resected using a microscope-based neuronavigation system. A sole defectively beta-hemolytic Streptococcus pyogenes was isolated from the lesion. The patient's peripheral blood whole-exome and the pathogen's whole-genome sequencing were performed respectively, revealing a heterozygous mutation in the interferon regulatory factor-8 (IRF8) gene in the patient and lack of hyaluronic acid capsules in Streptococcus pyogenes (genotype emm22). The patient eventually recovered after prompt surgical drainage of the abscess and appropriate antibiotic treatment. Conclusions It is important to pay attention to Streptococcus pyogenes brain abscesses with mild clinical manifestations. Upon reviewing all the cases of pediatric GAS brain abscess reported in the published literature, we discovered that early diagnosis and treatment are crucial factors that impact the prognosis of GAS brain abscess.